Social Support and Self-Efficacy in The Maintenance of Oral and Dental Health Among The Elderly - Anggita Nicky Shabrina; Silvia Prasetyowati; Isnanto (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2025)
Elderly individuals commonly experience physiological, psychological, and social changes that hinder their ability to maintain optimal oral and dental health. Low self-efficacy, combined with insufficient social support, has been identified as a major contributor to poor oral-health behaviors among older adults, particularly in underserved rural communities. This study aimed to analyze the relationship between social support and self-efficacy in maintaining oral and dental health among elderly residents in Sebalong Village, Nguling District, Pasuruan, in 2024. An analytical cross-sectional design was employed, involving 33 elderly participants selected through simple random sampling. Data were collected using two standardized instruments: the Social Support Questionnaire (SSQ) and the Geriatric Self-Efficacy Scale for Oral Health (GSEOH), both of which demonstrated high reliability. Descriptive statistics were used to categorize social support and self-efficacy levels, while Spearman’s rank correlation test was applied to examine the relationship between the variables. The findings indicated that most respondents received moderate social support (mean = 13.78), whereas their self-efficacy levels were predominantly low (mean = 29.0). The correlation analysis showed a statistically significant positive relationship between social support and self-efficacy (p = 0.028; r = 0.383), suggesting that higher social support is associated with improved confidence in performing oral-health maintenance behaviors. These results highlight the need for community-based interventions that strengthen emotional, instrumental, informational, and esteem support for elderly individuals. Enhancing social support networks may serve as a practical strategy to improve oral-health behaviors and overall well-being among older adults in rural settings. Strengthened collaboration among families, local health workers, and community programs is recommended to ensure sustainable improvements in elderly oral-health maintenance.